A-5 Examining the Interactive Effects of Traumatic Brain Injury and Apolipoprotein E on Cognitive Decline in Alzheimer's Disease. (30th August 2021) - Alexander, Claire; Suhr, Julie
Abstract: Objective: Little research has focused on possible effects of TBI on cognitive decline rate after Alzheimer's disease (ad ) diagnosis. We examined whether Apolipoprotein E (APOE) status and TBI history interact to predict cognitive decline. Method: We used data from the National Alzheimer's Coordinating Centers (N = 463; 42.3% APOE e4 carriers, 7.8% with TBI history, mean baseline age 79.3). Inclusion criteria included normal cognition at baseline with diagnosis of ad at a follow-up visit; baseline age 50 or older; and at least 3 years of follow-up data. Mixed models (random intercept, random slope) were used, with TBI history, APOE status, and their interaction as predictors of interest. Education, race, and history of TIA, stroke, or hypertension were included as covariates. Cognitive measures included mental status exam scores and immediate/delayed story memory. Results: After accounting for covariates, TBI history had a positive effect on cognitive decline rate on the screener and immediate memory measures. APOE status did not affect rate of cognitive decline on the screener, but presence of e4 predicted faster decline on immediate and delayed memory. TBI history and APOE status interacted to predict delayed memory decline, such that history of TBI was associated with a reduced rate of decline for e4 non-carriers but there was no effect of TBI for e4 carriers. Conclusion: When examining cognitive decline trajectory, TBI history predicted slower decline (a positive effect) while APOE had either a negative impact or no effect, depending on the measure. Future study should examine cognitive decline in the context of demographic and genetic factors.